Comparative Analysis of Adiponectin and Leptin Levels in Obese and Non Obese PCOS Cases - Saira Kiran, Fouzia Shafi, Sardar Ahmad, Maryam Saeed, Tahira Rizwan, Shazia Hameed (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Polycystic Ovary Syndrome (PCOS) represents a complex endocrine disorderfrequently complicated by obesity and metabolic dysregulation. Adipokines such as adiponectin and leptin play critical roles